(untitled) (Entrepreneurship Journal for Finance and Business, 2020)
The banking crisis occurs in the banking system when cash withdrawals from all types of bank accounts by bank customers suddenly rise, that is, when the bank’s or financial institution’s liabilities are greater than financial assets and then its inability to cover the liabilities, then the cash and its equivalents are not guaranteed. The quality of the loan portfolio and the increase in bad loans from it have an impact on the financial position, and for this reason and in the aftermath of the recent financial crisis (2008), the International Accounting Standards Board, in cooperation with international organizations, issued the International Financial Reporting Standard (9) to recalculate the expected credit losses of financial instruments according to scientific grounds To avoid defaulting in debt repayment, the research focused on the challenges facing commercial and Islamic banks in Iraq in implementing the guiding regulations issued by the Central Bank of Iraq, which mandated the application of the standard as of 2019 in light of the capabilities available in those banks. With the aim of the research to shed light on the requirements of the standard IFRS-9) and procedures for banks in the application of the standard and the role of the Central Bank of Iraq in monitoring banks to ensure that those requirements are met. The research reached several conclusions, the most important of which is that the timing of the application of the standard is not appropriate due to the circumstances that Iraq is going through, and many commercial activities have stopped due to the outbreak of the Corona virus with the decline in oil prices. 2019 until a later time until the appropriate environment for the application is available